Indonesia Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan LKPD Terhadap Keterampilan Berpikir Kreatif Materi Larutan Asam Basa Pada Siswa Kelas XI IPA SMAN 2 Pujut - Indriani, Muhajeng Wahyu; Loka, I Nyoman; Muti’ah, Muti’ah (FKIP University of Mataram, 2024)
This research aims to determine the effect of using the guided inquiry learning model assisted by LKPD on creative thinking skills in acid-base solution material in class XI IPA students at SMAN 2 Pujut compared to using the conventional learning model. The method used in the research was a quasi-experiment with a pretest-posttest control group design. Sampling was carried out using cluster random sampling. The research sample consisted of class XI IPA 1 with 24 students as the experimental class and class XI IPA 2 with 24 students as the control class. The data in this research is creative thinking skills data collected using test techniques. The results of the data analysis showed that the average post-test score for the experimental group was 73.29 and the control group was 57.17. The t-test results show that the tcount is 1.93 > ttable 1.68 with a significance level of 5%. This shows that there is a positive and significant influence of the guided inquiry learning model assisted by LKPD on students' creative thinking skills.